Plasma Kallikrein as a Modulator of Liver Injury/Remodeling - Ahmed, Ibrahim A; Jaffa, Miran A; Moussa, Mayssam; Hatem, Duaa; El-Achkar, Ghewa A; Al Sayegh, Rola; Karam, Mia; Hamade, Eva; Habib, Aida; Jaffa, Ayad A (Frontiers in Pharmacology, 2021)
The occurrence and persistence of hepatic injury which arises from cell-death and inflammation results in liver disease. The processes that lead to liver injury progression and resolution are still not fully delineated. The plasma kallikrein-kinin system (PKKS) have been shown to play diverse functions in coagulation, tissue injury and inflammation but its role in liver injury has not been defined yet. In this study, we characterized the role of the PKKS at various stages of liver injury in mice as well as the direct effects of plasma kallikrein (PKall) on human hepatocellular carcinoma cell line (HepG2). Histological, immunohistochemical, and gene expression analyses were utilized to assess cell injury to inflammatory and fibrotic factors. Acute liver injury triggered by carbon tetrachloride (CCl4) injection, resulted in significant upregulation of gene expression of PKall, which was highly associated with HMGB1 gene, the marker of cell death, (PKall, r = 0.75, p < 0.0005, n = 7). In addition, increased protein expression of PKall was observed as clusters around necrotic areas. PKall treatment significantly increased the proliferation of CCl4-induced HepG2 cells and induced a significant increase in the gene expression of protease-activated receptor (PAR1), interleukin-1β (IL-1β), and galectin-3 (p < 0.05, n = 4). Temporal variations in stages of liver fibrosis were associated with an increase in the mRNA levels of B1R and B2R genes (p < 0.05; n = 3-10). In conclusion, these findings indicate that PKall may play diverse roles in liver injury, inflammation, and fibrosis and suggests that PKall may be a target for intervention in states of liver injury.